METHOD DEVELOPMENT AND VALIDATION OF A REVERSED-PHASE LIQUID CHROMATOGRAPHIC METHOD FOR THE SIMULTANEOUS ESTIMATION OF SELECTED ANTIDIABETIC DRUGS IN THE PRESENCE OF THEIR DEGRADATION PRODUCTS - Nc, Kotecha; Jk, Patel (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was designed to conduct forced degradation and validation studies for the simultaneous estimation of metformin, sitagliptin, pioglitazone, and glimepiride. Methods: Analytes were separated on an Agilent XDB-C18, 150 × 4.6 mm, 5 μm column using an isocratic elution mode having mobile phase composition of 20 mM potassium dihydrogen phosphate buffer (pH 4.0):acetonitrile (65:35% v/v). Analytes were detected at a wavelength of 225 nm. The optimized method was validated as per the ICH Q2 guidelines. Results: The retention times of metformin, sitagliptin, pioglitazone, and glimepiride were 3.47, 4.83, 5.83, and 9.44 min, respectively. The linearity was 25–100 μg/ml for metformin, 2.5–10 μg/ml for sitagliptin, 1–4 μg/ml for pioglitazone, and 0.75–3 μg/ml for glimepiride. The correlation coefficient for calibration curves was >0.99, and accuracy was between 98 and 102% for each analyte. Inter- and intra-day precisions were calculated <2% relative standard deviation for each analyte. Conclusion: A significant degradation was observed in the presence of acidic, basic, neutral, oxidative, and photolytic stress conditions. The method is simple, precise, accurate, robust, and reproducible and was able to successfully separate and quantify metformin, sitagliptin, pioglitazone, and glimepiride in the presence of their degradation products.